2013
DOI: 10.1155/2013/409321
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effect of Procyanidins from Wild Grape (Vitis amurensis) Seeds in LPS-Induced RAW 264.7 Cells

Abstract: In the present study, the anti-inflammatory effect and underlying mechanisms of wild grape seeds procyanidins (WGP) were examined using lipopolysaccharide- (LPS-) stimulated RAW 264.7 cells. We used nitric oxide (NO) and prostaglandin E2 (PGE2) and reactive oxygen species (ROS) assays to examine inhibitory effect of WGP and further investigated the mechanisms of WGP suppressed LPS-mediated genes and upstream expression by Western blot and confocal microscopy analysis. Our data indicate that WGP significantly r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
0
12

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 58 publications
2
52
0
12
Order By: Relevance
“…blood CRP concentration) in type-2 diabetic patients at high risk for cardiovascular disease (Kar et al, 2009). Procyanidins from wild grape seed significantly reduced LPS-induced inflammation by regulating the NFκB pathway (Bak, Truong, Kang, Jun, & Jeong, 2013). Collectively, these data suggest that flavonoid-rich ChrSd diet may potentiate the antioxidant activity and lower HF dietinduced oxidative stress and inflammation by down-regulating the genes related to scavenging ROS, ER stress, NFκB pathway, and immune and inflammatory responses in the adipose tissue.…”
Section: Discussionmentioning
confidence: 87%
“…blood CRP concentration) in type-2 diabetic patients at high risk for cardiovascular disease (Kar et al, 2009). Procyanidins from wild grape seed significantly reduced LPS-induced inflammation by regulating the NFκB pathway (Bak, Truong, Kang, Jun, & Jeong, 2013). Collectively, these data suggest that flavonoid-rich ChrSd diet may potentiate the antioxidant activity and lower HF dietinduced oxidative stress and inflammation by down-regulating the genes related to scavenging ROS, ER stress, NFκB pathway, and immune and inflammatory responses in the adipose tissue.…”
Section: Discussionmentioning
confidence: 87%
“…During inflammation responses, microglia as the principle effectors of immune system in the brain, release pro-inflammatory cytokines which directly affects neuronal function including long-term potentiation, glutamate release and cell signaling pathways 24 . LPS has been shown that triggers the overproduction of pro-inflammatory cytokines such as TNF α , IL-1β , IL-6 13,25 . It has also been reported that IL-1 receptors antagonist ameliorates learning and .…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have reported that LPS increases the production of mediators such as NO, prostaglandin E2 (PGE2) and reactive oxygen species (ROS) through stimulating the macrophages 13 . LPS also increases the level of NO through promoting the release of pro-inflammatory cytokines such as TNF-α and IL-1β from macrophages and leucocytes 14 .…”
mentioning
confidence: 99%
“…Since that time, polyphenolic compounds as active ingredients in skin products with different applications have been reported that cover all three criteria proposed by Kilgman [52,53,54]. As for the first benchmark, resveratrol, 4′ acetoxy resveratrol, racemic equol, R -equol and S -equol have been shown to penetrate human skin at effective concentrations using standard solubilizing agents [19,27,55,56,57].…”
Section: Human Skin Gene Expressionmentioning
confidence: 99%